Students’ Perceptions toward a Conversational Class Taught By Foreigner Counterpart - Nurul Inayah (IAIN Salatiga, 2013)
This research is aimed at knowing what the students‘ perception of having taught by foreigner counterpart (native speaker of English) in a conversational class. Besides elaborating the students‘ perception which affects how they act and behave during the teaching and learning process, this research also wants to explore the students‘ difficulties and strategies in facing the foreigner‘s class. Then, the students‘ expectation of an ideal conversational class is also important to be investigated in order to conduct a better one in the future. Since this research explores the students‘ perception which come from the students‘ experience, qualitative approach is considered as an appropriate research design. Then the result of this research is presented descriptively in order to reveal the students‘ perception comprehensively. The findings of this research show that most of the students give high appreciation with the presence of foreigner. In fact, the personality of the foreigner as a teacher is also very important to be highlighted since it gives significant influence on students‘ perception. The personality and skill in classroom management become reasons for the other students who do not like the foreigner. Then, the cross cultural understanding and the ability to communicate in English is the students‘ main difficulty that hinders their teaching and learning process. Keywords: perception; conversational class; Foreign conterparts